Bimbingan Sosial Berbasis Prinsip Islam Dalam Meningkatkan Interaksi Sosial Positif Siswa di Kolej Vokasional Nibong Tebal Malaysia - Ulfani, Mutia; Zain, Arifin; Nk, Mahdi (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Social interaction plays a crucial role in education as it fosters communication skills and emotional intelligence, essential for personal and professional growth. Additionally, interacting with peers and educators in a learning environment enhances understanding and knowledge retention, supporting collaborative learning and problem-solving skills. This study aims to explore social guidance based on Islamic principles implemented by students of Islamic Counseling at Nibong Tebal Vocational College, located at Jalan Bukit Panchor, 14300 Nibong Tebal, Penang, Malaysia. The research was designed to help individuals identify, handle, and overcome social issues, enabling them to adapt well within their social environments. Data collection involved direct observations and interviews with lecturers and students at the college. During the implementation, students guided classroom discussions and activities in open areas like reading gardens. The results showed a significant improvement in social interactions, including greetings, smiles, salutations, and handshakes. The guidance provided has also been integrated into the students' daily lives, enhancing their understanding and awareness of both positive and negative social interactions, and developing empathy, social care, and good social character